The Influence of Brand Equity, Perceived Quality, and Emotional Attachment on Repurchase Intention of Local Coffee Products in Ambon - Tubalawony, Jacsy (Westscience Press, 2025)
This study investigates the influence of brand equity, perceived quality, and emotional bonding on repurchase intention for local coffee products in Ambon, Indonesia. Using a quantitative research approach, data were collected from 155 respondents who had previously purchased local coffee products. The research instrument employed a five-point Likert scale, and data analysis was conducted using SPSS version 25, including validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results show that brand equity, perceived quality, and emotional bonding all have positive and significant effects on repurchase intention, with emotional bonding being the most dominant factor. This suggests that consumers’ emotional connection to local coffee brands strongly influences their loyalty and repeat purchasing behavior. The findings highlight the importance of integrating brand identity, product consistency, and emotional engagement in marketing strategies to strengthen customer relationships and sustain the local coffee market in Ambon. The study contributes to both theoretical understanding and practical marketing applications by demonstrating how emotional and cognitive factors jointly shape consumer loyalty in local product contexts.